2018
DOI: 10.1080/14647893.2017.1354843
|View full text |Cite
|
Sign up to set email alerts
|

Towards a developing construct in dance education – exploring the relation of emotional intelligence to teacher’s sense of efficacy and teaching experience among dance education student teachers in the United Kingdom

Abstract: Towards a developing Construct in Dance Education-Exploring the Relation of Emotional Intelligence to Teacher's Sense of Efficacy and teaching Experience among British Dance Education Students. Theories of emotional intelligence (EI) have already been applied successfully in the field of education, and EI has been found to predict different aspects of teaching such as influencing one's self-beliefs. Positive associations among emotional intelligence (EI) and teachers' self-efficacy (TSE) and length of teaching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 59 publications
3
16
0
1
Order By: Relevance
“…Considering the relationships between the two constructs, teachers better skilled at perceiving and understanding emotions as well as expressing and classifying, managing and regulating them reveal higher levels of teacher efficacy (Hypothesis 6). This relationship is positive and statistically significant and it supports previous findings linking EI with higher levels of teacher efficacy [1,8,9,11]. Emotionally intelligent teachers have the skills to perceive their students beyond their behaviors and results.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Considering the relationships between the two constructs, teachers better skilled at perceiving and understanding emotions as well as expressing and classifying, managing and regulating them reveal higher levels of teacher efficacy (Hypothesis 6). This relationship is positive and statistically significant and it supports previous findings linking EI with higher levels of teacher efficacy [1,8,9,11]. Emotionally intelligent teachers have the skills to perceive their students beyond their behaviors and results.…”
Section: Discussionsupporting
confidence: 87%
“…Besides, some researches have demonstrated a positive link between EI and teacher efficacy [1,8,9,11]. In sum, teacher EI also affects the way they think and develop efficacy beliefs about teaching.…”
Section: Teachers' Emotional Intelligencementioning
confidence: 98%
See 1 more Smart Citation
“…Also, teachers recognized the importance of EI in classrooms and how it becomes a crucial constituent of the teaching-learning process resulting in holistic learning and development of students (Allen et al, 2014;Becker et al, 2014;Maamari & Majdalani, 2019;Pugazhenthi & Srinivasan, 2018). Besides, different studies showed that EI is positively correlated with teacher's efficacy (Hassan et al, 2015;Koçoğlu, 2011;Wenn et al, 2018), and with classroom management efficacy (Valente et al, 2019;Wahyuddin, 2016).…”
Section: Teacher's Emotional Intelligence Capacitiesmentioning
confidence: 99%
“…Good dance education development can greatly expand and cultivate the imagination and creativity of college students, and play an irreplaceable role in this training process compared with other disciplines (Hogg et al, 2012). At the same time, implementing dance education, as an important means of aesthetic education system in colleges and universities, involves the function of shaping students' personality and enlightening their intellectual development (Wenn, Mulholland, Timmons, & Zanker, 2018).…”
mentioning
confidence: 99%